Evaluating the content validity of instruments for measuring principal’s ethical leadership practices using the Content Validity Ratio (CVR) method - Mackencidy Bujang; Bity Salwana Alias; Azlin Norhaini Mansor (Penerbit Universiti Kebangsaan Malaysia, 2025)
The principal’s ethical leadership practices are crucial for developing an excellent school. By embodying ethical values such as honesty, integrity, and responsibility, principals inspire students and staff to act ethically. Ethical principal ensures fairness in school management, attend to the needs of all stakeholders, and engage in open and effective communication. Although several measurement instruments assess ethical leadership, those with good validity are limited, especially for evaluating principals. This study aims to test the content validity of the Principal’s Ethical Leadership instrument using Lawshe's (1975) Content Validity Ratio (CVR) analysis. An online survey was conducted with five experts selected through purposive sampling, including individuals with backgrounds in educational management and administration from the Ministry of Education, state education departments, and school leaders. The instrument's validity involves seven constructs and 38 main items based on the Ethical Leadership at Workplace (ELW) model by Kalshoven et al. (2011). The study found that the instrument has good content validity, with 34 items reaching the minimum CVR value (N=5, CVRcritical=0.916). Three items that did not reach the minimum CVR value were improved, and one item was dropped, resulting in 37 refined items in the final instrument. This instrument has the potential to be a valuable tool for measuring ethical leadership practices among school leaders in Malaysia. A pilot study is recommended, with data analyzed using more in-depth statistical analysis such as SEM-PLS to refine items further and ensure the instrument's reliability and accuracy.